Molybdenum–Manganese hydroxide microcubes based electrode via hydrothermal method for asymmetric supercapacitor. Issue 19 (1st October 2022) - Teli, A.M.; Beknalkar, S.A.; Bhat, T.S.; Mane, S.M.; Shin, J.C.
Abstract: An electrode with multi electron surfaces facilitates more redox sites during charge storage reaction in the case of transition metal oxides used in supercapacitor application. Molybdenum (Mo) oxide and manganese (Mn) oxide have high theoretical capacitance; this study focused on depositing Mo–Mn together in a single mixed metal oxide. Here, Mo–Mn hydroxide was deposited on Ni-foam by a single-step hydrothermal method. The X-ray photoelectron spectroscopy confirms the presence of Mo and Mn in 4 + and 3 + oxidation states, respectively. The different size of Mo–Mn hydroxide microstructures was observed with varying deposition time. The porous cubes-like microstructure exhibited high areal capacitance of 88.6 mF cm −2 with energy density of 3.08 μWh·cm −2  at 125 μW cm −2 power density within a kinetic potential. This microcubes-like structures and activated carbon were used as positive and negative electrodes, respectively, to fabricate an asymmetric supercapacitor (ASS) device. The ASS device showed capacitance retention of 87% (∼5, 000 cycles) and excellent Coulombic efficiency (96%) with energy density of 5.6 μWh·cm −2  at 1.12 mW cm −2 power density at 1.8 V potential.